2014
DOI: 10.1016/j.jval.2014.08.2112
|View full text |Cite
|
Sign up to set email alerts
|

Costs of Psoriasis in Europe. A Systematic Review of the Literature

Abstract: Objectives: Chronic idiopathic (or spontaneous) urticaria (CIU) is estimated to occur in 0.3% of the general population in Turkey. Although the burden of the disease is substantial for the payer, there has been no cost-analysis performed in our country. The purposes of this study are to determine the resources and costs related to the diagnosis and treatment of patients with CIU, and to estimate the annual economic burden to the Social Security Institution (SGK). MethOds: Delphi technique was applied to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
1
4
0
1
Order By: Relevance
“…Our findings showed that medication appeared to be most significant aspects (90%) and this is in line with previous analysis conducted in European countries (Beyer & Wolverton 2010;Obradors et al 2014). Productivity loss is not uncommon among psoriasis patients.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings showed that medication appeared to be most significant aspects (90%) and this is in line with previous analysis conducted in European countries (Beyer & Wolverton 2010;Obradors et al 2014). Productivity loss is not uncommon among psoriasis patients.…”
Section: Discussionsupporting
confidence: 92%
“…In Germany, Steinke et al (2013) revealed that yearly costs per patient added up to RM38,844.34 (€7,092.00). In a systematic review, Obradors et al (2014) discovered that the annual total cost of the treatment of psoriasis in Europe (from the social perspective) was between RM6,349.00 (€1,340.00) and RM39,104.00 (€8,253.00). Because our health care system is heavily subsidised, the estimated costs of the treatment of psoriasis are far lower than other countries.…”
Section: Discussionmentioning
confidence: 99%
“…Si bien la introducción de TB parece contribuir a la disminución de costes hospitalarios en el manejo de la Ps, con una reducción de 2.357 D vs 564 D paciente-año (euros de 2013, equivalente a 2.902 a 695 USD-PPP paciente-año) 35 , el incremento en el coste directo y total identificado en los estudios 23,25,33 de Ps y APs, muestran el enorme impacto económico que supone su incorporación en el arsenal terapéutico. El efecto de la introducción de TB ha sido valorado con anterioridad en Europa 36---38 .…”
Section: Discussionunclassified
“…2). Total direct costs in diabetes were €93.0 billion compared with €70.0 billion in oncology and €57.2 billion in autoimmune disease, whereas drug costs were €6.4 billion (7% of total spend), €26.3 billion (38%) and €12.0 billion (21%), respectively [6,42,46,[52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69]. However, at the per-patient level, oncology was associated with the highest total costs (Fig.…”
Section: Economic Burden Findingsmentioning
confidence: 99%
“…However, at the per-patient level, oncology was associated with the highest total costs (Fig. 2), with a mean annual drug spend of €2789 for oncology, €937 for autoimmune diseases and €247 for diabetes, highlighting the huge incremental costs associated with oncology medication [6,42,46,[52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69].…”
Section: Economic Burden Findingsmentioning
confidence: 99%